Sugar glass fugitive ink loaded with calcium chloride for the rapid casting of alginate scaffold designs. Issue 7 (July 2018) - Gauvin-Rossignol, Gabrielle; Legros, Philippe; Ruel, Jean; Fortin, Marc-André; Bégin-Drolet, André
Abstract: Alginate-based hydrogels are widely used for the development of biomedical scaffolds in regenerative medicine. The use of sugar glass as a sacrificial template for fluidic channels fabrication within alginate scaffolds remains a challenge because of the premature dissolution of sugar by the water contained in the alginate as well as the relatively slow internal gelation rate of the alginate. Here, a new and simple method, based on a sugar glass fugitive ink loaded with calcium chloride to build sacrificial molds, is presented. We used a dual calcium cross-linking process by adding this highly soluble calcium source in the printed sugar, thus allowing the rapid gelation of a thin membrane of alginate around the sugar construct, followed by the addition of calcium carbonate and gluconic acid δ-lactone to complete the process. This innovative technique results in the rapid formation of "on-demand" alginate hydrogel with complex fluidic channels that could be used in biomedical applications such as highly vascularized scaffolds promoting pathways for nutrients and oxygen to the cells.